2022
DOI: 10.1039/d2dt00476c
|View full text |Cite
|
Sign up to set email alerts
|

Recent findings and future directions in photosynthetic hydrogen evolution using polypyridine cobalt complexes

Abstract: The production of hydrogen gas using water as the molecular substrate currently represents one of the most challenging and appealing reaction schemes in the context of Artificial Photosynthesis (AP), i.e.,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 101 publications
(211 reference statements)
0
29
0
Order By: Relevance
“…A fixed concentration of both QDs (0.11 mM) and ascorbate (0.5 M) was used in all photochemical tests. The experimental data obtained in terms of moles of hydrogen produced as a function of the irradiation time (kinetic traces) were properly employed in order to extract the relevant photocatalytic parameters [ 5 ]: (i) the maximum turnover number (TON) calculated as the ratio between the maximum quantity of hydrogen produced (in moles) and the quantity of catalyst employed (in moles), (ii) the maximum turnover frequency (TOF/h −1 ) calculated as the ratio between the initial rate of hydrogen production (in mol/h, estimated in the linear portion of the kinetic trace) and the moles of catalyst, and (iii) the quantum efficiency (QE/%) calculated as the ratio between two-times the initial rate of hydrogen formation (in mol/h) and the absorbed photon flux (in Einstein/h).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A fixed concentration of both QDs (0.11 mM) and ascorbate (0.5 M) was used in all photochemical tests. The experimental data obtained in terms of moles of hydrogen produced as a function of the irradiation time (kinetic traces) were properly employed in order to extract the relevant photocatalytic parameters [ 5 ]: (i) the maximum turnover number (TON) calculated as the ratio between the maximum quantity of hydrogen produced (in moles) and the quantity of catalyst employed (in moles), (ii) the maximum turnover frequency (TOF/h −1 ) calculated as the ratio between the initial rate of hydrogen production (in mol/h, estimated in the linear portion of the kinetic trace) and the moles of catalyst, and (iii) the quantum efficiency (QE/%) calculated as the ratio between two-times the initial rate of hydrogen formation (in mol/h) and the absorbed photon flux (in Einstein/h).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen production via light-driven water splitting is recognized as a candidate fundamental reaction for the generation of clean fuels [ 1 , 2 ]. For this purpose, one of the simplest approaches envisions the coupling in an aqueous solution of three molecular components, namely a light-harvesting sensitizer, a hydrogen evolving catalyst (HEC), and an electron donor [ 3 , 4 , 5 ]. Ideally, this latter component should be constituted by the water molecule itself, leading to the production of oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Control experiments performed in absence of one of each component (Table 1, Figure S3) confirmed that no H 2 evolved when any one of them were absent from the catalytic mixture. Notably, no photocatalytic activity was observed in absence of TCEP, although many hydrogen evolution systems based on ruthenium‐based photosensitisers and cobalt‐based catalysts are reported to operate with solely HAsc – as sacrificial electron donor [30] …”
Section: Resultsmentioning
confidence: 99%